2008
DOI: 10.1039/b716418c
|View full text |Cite
|
Sign up to set email alerts
|

Internal friction of single polypeptide chains at high stretch

Abstract: Experiments that measure the viscoelasticity of single molecules from the Brownian fluctuations of an atomic force microscope (AFM) have provided a new window onto their internal dynamics in an underlying conformational landscape. Here we develop and apply these methods to examine the internal friction of unfolded polypeptide chains at high stretch. The results reveal a power law dependence of internal friction with tension (exponent 1.3 +/- 0.5) and a relaxation time approximately independent of force. To exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
94
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(110 citation statements)
references
References 16 publications
11
94
5
Order By: Relevance
“…We can directly compare our results with those of Khatri et al (13), who reported a value of k i L i y1 À 2 nN (a spring constant normalized on the stretched module length L i ) for the same protein. Correspondingly, taking the value of L i to be~20-30 nm, we obtain a much larger value, not smaller than~30 mN/m, for the spring constant of the I27 protein.…”
Section: Resultssupporting
confidence: 61%
See 4 more Smart Citations
“…We can directly compare our results with those of Khatri et al (13), who reported a value of k i L i y1 À 2 nN (a spring constant normalized on the stretched module length L i ) for the same protein. Correspondingly, taking the value of L i to be~20-30 nm, we obtain a much larger value, not smaller than~30 mN/m, for the spring constant of the I27 protein.…”
Section: Resultssupporting
confidence: 61%
“…Note also that a persistence length of the protein as small as 0.25 nm (we believe this is too small; cf. the data given in (39)) was invoked by Khatri et al (13) to explain their observation.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations